1990
DOI: 10.1007/bf00436507
|View full text |Cite
|
Sign up to set email alerts
|

Oral yeasts in patients with cancer of the mouth, before and during radiotherapy

Abstract: The yeasts of patients with oral cancer has been studied before and during Xr-therapy. Gram and PAS smears revealed an increase of yeast-like structures, during treatment, from 56% to 66% of the cases. Before radiotherapy oral yeasts were isolated from 56% of the patients with cancer represented by Candida albicans (30%); C. tropicalis (12%); C. glabrata and C. krusei (4%), besides six other different species (2%). During radiotherapy yeasts were isolated in 72% of the cases, as follow: C. albicans (36%); C. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
3
16
0
10
Order By: Relevance
“…virulence factors, proteinase and phospholipase activities have been extensively studied as they can play an important role in the pathogenesis of the candidosis. The determination of the enzymatic activity of C. albicans and other species isolated from different anatomic sites was observed by several authors (17,19,21,24). These studies showed a variation from 60 to 100% of isolates with proteinase activity and 50 to 100% for phospholipase activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…virulence factors, proteinase and phospholipase activities have been extensively studied as they can play an important role in the pathogenesis of the candidosis. The determination of the enzymatic activity of C. albicans and other species isolated from different anatomic sites was observed by several authors (17,19,21,24). These studies showed a variation from 60 to 100% of isolates with proteinase activity and 50 to 100% for phospholipase activity.…”
Section: Discussionmentioning
confidence: 94%
“…In this work, C. tropicalis was the second most frequently isolated specie. Paula et al (19) reported that 16% of the isolates from the oral cavity of patients with cancer during radiotherapy belonging to the genus Candida were identified as C. tropicalis. This result is similar to the value obtained in this study (20.42%), despite the absence of such predisposing factor among the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reconhecidamente, esses pacientes apresentam higiene oral deficitária, muitas vezes dificultada por tumores volumosos, evidenciada pela predominância do estádio avançado encontrado e pelo perfil tabagista crônico, que também é contributivo para a colonização fúngica. Um estudo que avaliou comparativamente a colonização por Candida durante a RxT e a sua presença antes do tratamento evidenciou que 56% dos pacientes tinham Candida e que 30% das espécies foram classificadas como C. albicans (17) . Em outro estudo realizado por Reeding et al (20) (12) .…”
Section: Discussionunclassified
“…Em adição, idade, uso do tabaco, imunossupressão, higiene bucal deficiente e antibioticoterapia contribuem para o aumento da colonização de Candida em pacientes irradiados em cabeça e pescoço (15,22,26) . Durante o curso radioterápico, foi demonstrada a diversificação de espé-cies de Candida, bem como o aumento da incidência da colonização de espécies como Candida albicans e Candida tropicalis (17,20) . Mesmo após a RxT, com a continuidade da xerostomia, a quantificação de espécies de Candida pode ser alta (5) .…”
Section: Introductionunclassified
See 1 more Smart Citation